2020
DOI: 10.1007/s11356-020-11300-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity of oil sludges and residuals from their washing with surfactants: soil dehydrogenase and ryegrass germination tests

Abstract: Oil sludge washing (OSW) with surfactants and co-solvents is used to recover the oil, and this process leaves some residuals (sediments and surfactant solution). Currently, there are no data on the ecotoxicological effects of these OSW residuals from different sludges. This study evaluated the toxicity of OSW residuals from washing four types of oil sludges with five surfactants (Triton X-100 and X-114, Tween 80, sodium dodecyl sulphate (SDS) and rhamnolipid) and a co-solvent (cyclohexane). The toxicity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…DH is known as one of the most essential soil enzymes (Wolf et al 2020). DH activity showed a positive correlation with TPH degradation, and it was one of the most highly active enzymes in TPH-contaminated soil (Ramirez et al 2021). DH activity is used as an important indicator to evaluate the activity of soil microorganisms (Małachowska-Jutsz and Matyja 2019).…”
Section: Effect Of Novosphingobium Sp Cut1 Inoculation On Tall Fescue...mentioning
confidence: 98%
“…DH is known as one of the most essential soil enzymes (Wolf et al 2020). DH activity showed a positive correlation with TPH degradation, and it was one of the most highly active enzymes in TPH-contaminated soil (Ramirez et al 2021). DH activity is used as an important indicator to evaluate the activity of soil microorganisms (Małachowska-Jutsz and Matyja 2019).…”
Section: Effect Of Novosphingobium Sp Cut1 Inoculation On Tall Fescue...mentioning
confidence: 98%
“…There are two moieties of the rhamnolipids, one or two l -rhamnose hydrophilic molecules with a glycosidic linkage to the hydrophobic groups comprising one or multiple β-hydroxylated fatty acids. The diversity in chemical structures of RLs , features their wide-ranging functionalities. , In the past two decades, experimental studies have shown promising results of using RLs for environmental remediation. By improving the production method, the production cost of RL has become more suitable for massive usage. , Nevertheless, the naturally produced RLs usually contain several RLs homologues and congeners. Understanding the micellar properties and the interfacial behavior of RLs in their pure states or in mixtures, as well as their interactions with hydrocarbons, is the key to advance future development.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in biomass and microbial activity is influenced by low organic matter content and reduced nutrient supply (Ciarkowska & Gambus, 2020 ). Ramirez et al ( 2021 ) investigated the effect of soil fertilisation with sewage sludge contaminated with petroleum compounds with the addition of surfactants. The authors concluded that the non-fertilised soil showed the highest DHA value of over 200 µg INTF·g −1 DM·2 h −1 , while the addition of sewage sludge contaminated with surfactants to the soil reduced the DHA to at least 100 µg INTF·g −1 DM·2 h −1 , and to even below 50 µg INTF·g −1 DM·2 h −1 .…”
Section: Methodsmentioning
confidence: 99%
“…DHA is an indicator of soil health and is correlated with the number and diversity of soil microorganisms (Maurya et al, 2020). Soil DHA is usually analysed using two colorimetric methods: with 2,3,5-triphenyltetrazolium chloride (TTC) (Ciarkowska & Gambus, 2020;Hamidović et al, 2020;Lemanowicz et al, 2020;Uzarowicz et al, 2020) or with iodonitrotetrazolium formazan (INTF) (El Gouzi et al, 2015;Emmert et al, 2021;Hanajík et al, 2017;Ramirez et al, 2021). Poorer results for the TTC method have been reported due to the effects of drying, temperature, moisture and oxygen in the soil (Kumar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%